Capture and handling stress in incidentally captured rays from small-scale fishing: A physiological approach - Rangel, Bianca de Sousa; Rodrigues, Alexandre [UNESP]; Moreira, Renata Guimarães (Oecologia Australis, 2021)
Incidental capture is the most common threat to rays worldwide, by both artisanal and industrial fishing. To better understand this threat, we evaluated the capture and handling stress in three incidentally captured benthopelagic ray species: American cownose ray (Rhinoptera bonasus), Brazilian cownose ray (Rhinoptera brasiliensis), spotted eagle ray (Aetobatus narinari), and one benthic species, the longnose stingray (Hypanus guttatus). Through analyzing secondary stress physiological variables (plasma lactate and glucose), our results revealed a similar physiological stress response in benthopelagic rays, suggesting they are resilient to capture using beach seine fishing. We also demonstrated that handling for research can increase the stress in both American cownose and spotted eagle rays, suggesting that more stringent handling protocols for research should be required. Findings from this study expands on the number of ray species for which stress to capture and handling has been evaluated, providing recommendations for appropriate research and management.
Keywords: Batoid; Beach seine fishing; Elasmobranchs; Incidental capture; Non-lethal research; Stingrays